A guide for comparing microbial co‐occurrence networks. Issue 1 (10th January 2023) - Liu, Chi; Li, Chaonan; Jiang, Yanqiong; Zeng, Raymond J.; Yao, Minjie; Li, Xiangzhen
Abstract : The article provides a pipeline for comparing microbial co‐occurrence networks based on the R microeco package and meconetcomp package. It has high flexibility and expansibility and can help users efficiently compare networks built from different groups of samples or different construction approaches.